Ministry Of Trade and Industry Decree No. 1111 Of The Year 2016 = وزارة التجارة والصناعة قرار رقم 1111 لسنة 2016 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic